Description of Knowledge and Habits of Junk Food Consumption For Health in Adolescents in Sidoarjo Islamic Middle School - Rahmadhani, Novitrianah; Alfi Maziyah; Nooreena Yusop (Prodi keperawatan sidoarjo, politeknik kesehatan kemenkes surabaya indonesia, 2024)
Fast food is an alternative choice for people who are busy working and rarely have time to cook, so they need practicality by choosing ready-to-eat food. Frequent consumption of junk food can have a negative impact on adolescent health, namely certain diseases such as obesity, heart disease, cancer, hypertension, and kidney failure. The purpose of this study was to determine the knowledge and frequency of consumption habits of eating junk food in adolescents at Sidoarjo Islamic Middle School. This research is a descriptive study with a cross sectional approach. The subjects of this study were 79 respondents. The instrument used for data collection is in a digital form using Google Forms. Data on knowledge and frequency of junk food consumption habits can be obtained by means of a questionnaire technique. Data analysis was performed with descriptive statistical analysis. The results of the study revealed that the respondents had knowledge about fast food (junk food) among adolescents not enough as much 1 person student ( 1 %), R respondent with Enough as much 3 person student ( 4 %) , Respondents in the moderate category were 10 students (13 % ) and Respondents well amounted to 65 students (82 %) . It is to shows that there are more respondents whose ac-tions are good. And the results of the data for the frequency of consumption of fast food (junk food), on average students consume more fast food (junk food) 1-2x/month of all the types of food listed . Parents are expected to pay attention to their actions in giving ready-to-eat food to children, so that children can choose intelligently which foods will become their daily consumption.